Synthesis of Mannich N-bases based on benzimidazole derivatives using SiO2OAlCl2 catalyst and their potential as antioxidant, antibacterial, and anticancer agents - Antonius Herry Cahyana; Ikrimah Desta; Laely Amaliyah; Aida Nadia; Hilna Diana Sahaya; Dicky Annas; Bayu Ardiansah; Mohammad Jihad Madiabu; Inda Mapiliandari; Kang Hyun Park (South African Journal of Chemical Engineering)
This research aimed to synthesis of N-base compounds based on benzimidazole derivatives and their potential as antibacterials, antioxidants, and anticancer. The synthesis was conducted in two stages, namely the intermediate (benzimidazole derivatives) and the final product (N-mannich base), using five variations of organic acids and SiO2OAlCl2 as catalyst. The results showed that the catalyst was successfully synthesized and characterized by The Fourier transform infrared (FTIR), X-ray diffraction (XRD), and Scanning electron microscopy with energy dispersive X-ray spectroscopy (SEM-EDS). The purity of the synthesized compounds was monitored by Thin layer chromatography (TLC), melting point test, Ultraviolet-visible (UV–Vis), and Liquid chromatography-Mass spectrometry (LC-MS). The five intermediate compounds and five mannich base products yield 77 %-89 % and 65 %-85 %, respectively. The final products were applied through antibacterial testing against Staphylococcus aureus (Gram-positive bacteria) and Escherichia coli (Gram-negative bacteria) by disc diffusion. Mannich base compounds have potential antibacterial agents, but only 4A and 4E gave the best inhibition zone diameter. Meanwhile, the antioxidant testing result using the 1,1-diphenyl-2-picrylhydrazyl (DPPH) method showed the best activity in the mannich base compound 4E. The anticancer test result showed that the five mannich base compounds had potential as anticancer agents.